Solve this equation

Solve this equation

Tutors, please sign in to answer this question.

Hi Lakeyshia,

Let's begin by writing our equation: 3(4z - 1) - 2(2 + 8) = 3(2 + 1)

First, we'll combine all like numeric terms in the parentheses on both sides of the equation:

3(4z - 1) - 2(10) = 3(3)

Next, we'll do the multiplication operation indicated by the paretheses for each term on both sides of the equation (for the 1st parentheses we'll distribute (multiply) the 3 outside the parenthesis by each term inside the parenthesis):

12z - 3 - 20 = 9

Next, we'll combine our like numeric terms on the left side of the equation:

12z - 23 = 9

Next, we'll get rid of the -23 on the left side of the equation by doing the opposite operation of addition (adding 23 to both sides of the equation):

12z = 32

Next, we'll get rid of the 12 in front of the z on the left side of the equation by doing the opposite operation of division (dividing both sides of the equation by 12):

z = 32/12

Finally, we'll reduce the fraction value for z by dividing both numerator and denominator by the largest factor common to both 12 and 32 (we'll divide both numerator and denominator by 4):

z = 8/3 (our solution)

Thanks for submitting your question.

Regards, Jordan.

12z - 3 -2(10) = 3(3)

12z - 3 - 20 = 9

12z - 23 = 9

12z = 32

z = 32/12 = 8/3